THE ASCEND AND DESCEND OF COMMUNISM IN EAST-CENTRAL EUROPE: AN HISTORICALOPINIONATED ANALYSIS - Khan, Abdul Zahoor (European Scientific Journal, ESJ, 2015)
The year of 1989 marked a turning point in world history. During the last six months of that year, the world witnessed the collapse of communism in East-Central Europe. Two years later, communism was abolished in the Soviet Union, and that country began to fall apart. These changes were stunning and unprecedented in terms of their breadth, depth, and speed. In 1989, Hungary and Poland led the way, though cautiously. In February of that year, the Hungarian communist party leadership officially sanctioned the emergence of opposition parties the beginning of the end of the party’s monopoly of power. In Poland a few months later, after a long series of roundtable negotiations between the communist party leadership and the opposition, the regime agreed to partially contested elections to the country’s national legislature. Within the countries of East-Central Europe, the social, economic, and political changes were as fundamental as were those in France and Russia after their revolutions. In every country in the region the transition to Western style parliamentary democracy meant a fundamental restructuring of the political system, a proliferation of new interest groups and parties, and upheaval within the bureaucracy and administration. At the same time, all of these new regimes attempted an economic transition from centrally planned economies to market-oriented ones with increasing degrees of private ownership of property. Trying to accomplish both of these transitions simultaneously, from authoritarianism to pluralism and from plant to market, was a huge task, and the two occasionally pulled against each other.